Parental emotional and hands‐on work—Experiences of parents with a newborn undergoing congenital heart surgery: A qualitative study. Issue 4 (30th August 2019) - Thomi, Mirjam; Pfammatter, Jean‐Pierre; Spichiger, Elisabeth
Abstract: Purpose: To explore both mothers' and fathers' experiences from prenatal or postnatal diagnosis of their newborn's congenital heart disease (CHD) to the first discharge after heart surgery in a Swiss university children's hospital. Design and Method: A qualitative research approach, based on a constructivist paradigm, was applied to explore participants' experiences and perceptions. Parents of nine children with moderate to severe CHD participated in semistructured joint couple interviews. Data were analyzed inductively via an iterative process, following the steps of thematic analysis. Results: Between the child's CHD diagnosis and hospital discharge after neonatal cardiac surgery, the overarching theme for parents was being confronted with demanding emotional and hands‐on work. This parental work included four themes with subthemes: Parents had to tackle a route through an unknown hospital world from receiving the CHD diagnosis and experiencing delivery to attending to their child in the pediatric intensive care unit and during surgery, as well as during the transfer to and the stay on the pediatric cardiac unit. They experienced an at times challenging interplay with health care professionals, performed teamwork as the nuclear family and managed concerned relatives and friends. Practice Implications: Health care professionals should establish trustful relationships with parents, while accompanying families continuously, providing consistent, straightforward information, and expressing appreciation for the parents' exceptional emotional and hands‐on work. Health care professionals' awareness of parent's experiences is vital to compassionate family‐centered care.